Evaluasi User Experience pada Game League of Legends Wild Rift menggunakan Metode Cognitive Walkthrough - Endar Wahyu Pamungkas; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
League of Legends: Wild Rift is a MOBA (Multiplayer Online Battle Arena) game developed by the Riot Games system for Android and iOS. This game is a modified version of the PC game League of Legends. The new application or system certainly has a new and different look and experience for users of the game. Cognitive walkthrough is one method that can be used to evaluate usability in which users perform various task scenarios. Usability evaluation can be explained as a method of testing a system when the user performs with his own awareness in assessing the ease and error to be analyzed. User Experience must be designed as well as possible to suit and meet user demands. The lesson flow is like starting with a literature study, scenario planning, careful testing, followed by system analysis and data collection and analysis of results. The respondents used in this study were divided into 3 respondents who had never played the game League of Legends: Wild Rift and 3 people who had experience in playing the game League of Legends: Wild Rift and similar games. The results of the evaluation of the game League of Legends: Wild Rift have problems with its function (hiddendt) on the game select menu. However, this type of problem is light and easy to solve.